Alterations of the Gut Microbiome and Fecal Metabolome in Colorectal Cancer: Implication of Intestinal Metabolism for Tumorigenesis - Du, Xinhao; Li, Qing; Tang, Zhenzhen; Yan, Li; Zhang, Ling; Zheng, Qiao; Zeng, Xianghao; Chen, Guimei; Yue, Huawen; Li, Jun; Zhao, Ming; Han, Yuan-Ping; et al. (Frontiers in Physiology, 2022)
Abstract Objective- The gut microbiota and its metabolites are important for host physiological homeostasis, while dysbiosis is related to diseases including the development of cancers such as colorectal cancer (CRC). In this study, we characterized the relationship of an altered gut microbiome with the fecal metabolome in CRC patients in comparison with volunteers having a normal colorectal mucous membrane (NC). Methods- The richness and composition of the microbiota in fecal samples of 30 CRC patients and 36 NC controls were analyzed through 16S rRNA gene sequencing, and the metabolome was determined by ultra-performance liquid chromatography coupled to tandem mass spectrometry. Spearman correlation analysis was to determine the correlation between the gut microbiome and fecal metabolome in CRC patients. Results- There were significant alterations in the gut microbiome and fecal metabolome in CRC patients compared with NC controls. Bacteroidetes, Firmicutes, Actinobacteriota and Proteobacteria dominated the gut microbial communities at the phylum level in both groups. Compared with NC controls, CRC patients had a lower frequency of Blautia and Lachnospiracaea but a higher abundance of Bacteroides fragilis and Prevotella. Regarding the fecal metabolome, twenty-nine metabolites were identified as having significantly changed, showing increased levels of adrenic acid, decanoic acid, arachidonic acid, and tryptophan but a reduction in various monosaccharides in the fecal samples of CRC patients. Moreover, increased abundance of Bacteroides fragilis was strongly associated with decreased levels of monosaccharides, while Blautia was positively associated with the production of monosaccharides in the fecal samples. Conclusions- These results highlight alterations of gut microbiota in association with certain metabolites in CRC progression, implying potential diagnostic and intervention potential for CRC.